Same-sex teacher effects - Alexandra de Gendre; Jan Feld; Nicolás Salamanca; Ulf Zölitz (University of Zurich, Department of Economics, 2024)
The idea that students benefit from same-sex teachers has motivated policies around the world aimed at reducing gender inequalities. However, we do not know the size or generalizability of such same-sex teacher effects. We fill this gap by conducting a meta-analysis and our own study using data from 90 countries. Our meta-analysis summarizes the literature, highlights that estimates are difficult to compare because of differences in methods, and shows evidence of publication bias. Our multi-country study overcomes these shortcomings by providing many comparable estimates which are free of publication bias. Those estimates are ideal for learning about the generalizability of an effect. Our results reveal an interesting pattern. In primary education, effects vary substantially by country and outcome. In secondary education, same-sex teacher effects are near-universally positive for all countries and outcomes. Our paper showcases how we can use multi-country studies to learn about the generalizability of an effect.
Keywords: I21; I24; J24; 330; Same-sex teachers; role models; STEM; teachers; external validity; multi-country study; gender role models; standardized test scores; grades; job preferences; meta-analysis; meta-science